SYNTHESIS AND CHARACTERIZATION OF MAGNETIZED MULTILAYER GRAPHENE - Puca Pacheco, Mercedes (2021)
The present research aimed at the synthesis and characterization of magnetized multilayer graphene and for this, a 22 factorial design with a central point was proposed, to evaluate the effect of the size of the graphite nanoparticles and the magnetite / graphene mass ratio on magnetization. The magnetized multilayer graphene was obtained in two stages, in the first the graphite was sonified with sodium dodecyl sulfate (SDS) in aqueous medium and in the second stage the magnetite in situ coprecipitation was carried out, achieving the formation of multilayer graphene. By means of the analysis by Raman spectroscopy the formation ofmultilayer graphene was found. By means of the X-ray diffraction results, the crystalline phase of the magnetite and the degree of crystallinity were verified. By morphological analysis using the scanning microscope (SEM), the microstructural characteristics of these materials were confirmed. In conclusion, the magnetization of the composite material of graphene and magnetite does not depend on the mass ratio of magnetite / graphene because the graphene was magnetized and neither does it depend on the particle sizes of the sonified graphite and magnetized multilayer graphene.